Model Manajemen Kurikulum Pendidikan Islam Berbasis Kompetensi di Lembaga Pendidikan Islam - Azimah, Azimah (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the implementation of a competency-based Islamic education curriculum management model in Islamic educational institutions. The type of research used is library research. The data source in this study comes from secondary data collected from various relevant literature. The data analysis technique uses content analysis. The results of the study show that the application of the competency-based curriculum management model in Islamic educational institutions is carried out through several important stages, namely analysis of student needs, curriculum planning, curriculum implementation and evaluation. The main components in the competency-based curriculum management model in Islamic Education Institutions consist of core competencies and basic competencies, curriculum management, hidden curriculum, competency-based learning strategies, educational resources and facilities, competency-based evaluation and integration of Islamic values. The strategy of Islamic Education Institutions in integrating Islamic values with competency-based curriculum management models is curriculum planning based on Islamic values, teacher training to integrate Islamic values in learning, development of extracurricular activities that support Islamic values, the use of Islamic teaching materials, the application of active learning methods that reflect Islamic values and evaluation based on competencies and Islamic valuess